Supported Cobalt Nanoparticles for Hydroformylation Reactions. Issue 21 (19th March 2019) - Hertrich, Maximilian Franz; Scharnagl, Florian Korbinian; Pews‐Davtyan, Anahit; Kreyenschulte, Carsten Robert; Lund, Henrik; Bartling, Stephan; Jackstell, Ralf; Beller, Matthias
Abstract: Hydroformylation of olefins has been studied in the presence of specific heterogeneous cobalt nanoparticles. The catalytic materials were prepared by pyrolysis of preformed cobalt complexes deposited onto different inorganic supports. Atomic absorption spectroscopy (AAS) measurements indicated a correlation of catalyst activity and cobalt leaching as well as a strong influence of the heterogeneous support on the productivity. These new, low‐cost, easy‐to‐handle catalysts can substitute more toxic, unstable and volatile cobalt carbonyl complexes for hydroformylations on a laboratory scale. Abstract : Co catalysis : A new class of low‐cost, easy‐to‐handle materials for lab‐scale hydroformylation is reported. The pyrolysis of preformed Co complexes deposited onto inorganic supports resulted in immobilised cobalt nanoparticles for oxo synthesis. The most active materials Co/phen@TiO2 and Co/phen@C represent convenient reservoirs for active homogeneous cobalt species, and thus can substitute the common, but toxic, dicobaltoctacarbonyl complex.